MiR‐124a inhibits the proliferation and inflammation in rheumatoid arthritis fibroblast‐like synoviocytes via targeting PIK3/NF‐κB pathway. (3rd April 2019) - Yang, BiLing; Ge, Yan; Zhou, Yang; Wang, Jia; Xie, Xi; Li, Shu; Tang, Mengshi; Xu, LiChang; Tian, Jing
Abstract : Abnormal hyperplasia of fibroblast‐like synoviocytes (FLS) leads to the progression of rheumatoid arthritis (RA). This study aimed to investigate the role of miR‐124a in the pathogenesis of RA. The viability and cell cycle of FLS in rheumatoid arthritis (RAFLS) were evaluated by Cell Counting Kit 8 and flow cytometry assay. The expression of PIK3CA, Akt, and NF‐κB in RAFLS was examined by real‐time PCR and Western blot analysis. The production of tumour necrosis factor (TNF)‐α and interleukin (IL)‐6 was detected by ELISA. The joint swelling and inflammation in collagen‐induced arthritis (CIA) mice were examined by histological and immunohistochemical analysis. We found that miR‐124a suppressed the viability and proliferation of RAFLS and increased the percentage of cells in the G1 phase. miR‐124a suppressed PIK3CA 3'UTR luciferase reporter activity and decreased the expression of PIK3CA at mRNA and protein levels. Furthermore, miR‐124a inhibited the expression of the key components of the PIK3/Akt/NF‐κB signal pathway and inhibited the expression of pro‐inflammatory factors TNF‐α and IL‐6. Local overexpression of miR‐124a in the joints of CIA mice inhibited inflammation and promoted apoptosis in FLS by decreasing PIK3CA expression. In conclusion, miR‐124a inhibits the proliferation and inflammation in RAFLS via targeting PIK3/NF‐κB pathway. miR‐124a is a promising therapeutic target for RA.